Brain Activity Associated with the Illusion of Motion Evoked by Different Vibration Stimulation Devices: An fNIRS Study - Imai, Ryota; Nakano, Hideki; Morioka, Shu; Hayashida, Kazuki (Journal of Physical Therapy Science, 2014)
[Purpose] A number of different stimulation devices are used in basic and clinical research studies, and their frequencies of use vary. However, whether or not they are equally effective has not been investigated. The purpose of the present study was to investigate neural activity in the brain during the illusion of motion evoked by stimulating the tendons of the wrist extensor muscles using various vibration devices. [Subjects] Twelve right-handed university students with no history of nervous system disorder or orthopedic disease participated in the study. [Methods] The wrist extensor tendon was stimulated using 3 different devices: 1) a vibration stimulation device (SL-0105 LP; Asahi Seisakusho Co., Ltd., Saitama, Japan), frequency 80 Hz; 2) a handy massager (YCM-20; Yamazen Corporation, Osaka, Japan), frequency 70 Hz; and 3) a handy massager (Thrive MD-01; Thrive Co., Ltd., Osaka, Japan), frequency 91.7 Hz. Brain activity was recorded during stimulation by using functional near-infrared spectroscopy. [Results] Increased neural activity was observed in both the premotor cortices and the parietal region in both hemispheres in all 3 cases. The level and localization of neural activity was comparable for all 3 stimulation devices used. [Conclusion] This suggests that subjects experience the illusion of motion while the tendon is being stimulated using any vibration device.